H3K9ac and HDAC2 Activity Are Involved in the Expression of Monocarboxylate Transporter 1 in Oligodendrocyte - Lai, Qingwei; Du, Wantong; Wu, Jian; Wang, Xiao; Li, Xinyu; Qu, Xuebin; Wu, Xiuxiang; Dong, Fuxing; Yao, Ruiqin; Fan, Hongbin (Frontiers in Molecular Neuroscience, 2017)
Recently, it is reported that monocarboxylate transporter 1 (MCT1) plays crucial role in oligodendrocyte differentiation and myelination. We found that MCT1 is strongly expressed in oligodendrocyte but weakly expressed in oligodendrocyte precursors (OPCs), and the underlying mechanisms remain elusive. Histone deacetylases (HDACs) activity is required for induction of oligodendrocyte differentiation and maturation. We asked whether HDACs are involved in the regulation of MCT1 expression. This work revealed that the acetylation level of histone H3K9 (H3K9ac) was much higher in mct1 gene (Slc16a1) promoter in OPCs than that in oligodendrocyte. H3K9ac regulates MCT1 expression was confirmed by histone deacetylase acetyltransferase inhibitors trichostatin A (TSA) and curcumin. Of note, there was a negative correlation between H3K9ac and MCT1 expression in oligodendrocyte. Further, we found that the levels of HDAC1, 2 and 3 protein in oligodendrocyte were obviously higher than those in OPCs. However, specific knockdown of HDAC2 but not HDAC1 and HDAC3 significantly decreased the expression of MCT1 in oligodendrocyte. Conversely, overexpression of HDAC2 remarkablely enhanced the expression of MCT1. The results imply that HDAC2 is involved in H3K9ac modification which regulates the expression of MCT1 during the development of oligodendrocyte.